Marijuana Enforcement since Drug Policy Reform: An Exploration of Officer Discretion in Six States - Miller, J. Mitchell (American journal of criminal justice, 2022)
Marijuana enforcement remains a major point of entry to the criminal justice system despite broad state level reforms. The knowledge base on marijuana enforcement, however, is small and predates the current national decriminalization-legalization movement and is comprised almost entirely of survey data on officer attitudes regarding drug law, policy, and strategy, generally, rather than marijuana specifically. Focusing instead on officer self-reported behavior and expressed enforcement intent, multiple US COPS Office and US Bureau of Justice Assistance grants enabled focus group interview exploration of how marijuana enforcement has been impacted since policy reform. Data were obtained from 148 sworn officers in seven agencies across six states that indicated marijuana incident outcomes are heavily dependent on officer discretion. Incident resolution was observed primarily as a function of situational dynamics (suspect demeanor, quantity of marijuana, and impaired driving concern), suspect background, agency prioritization of marijuana enforcement, and whether jurisdictions were prosecuting marijuana cases. Decision to arrest was correlated with officers’ age, years on force, gender, and ideological outlook regarding drug enforcement priorities and tended toward informal resolution in general and more so with younger and female officers. Despite national arrest statistics indicating otherwise, these findings suggest drug policy reform is affecting some discretionary leniency and nonenforcement of marijuana in favor of reported shiftwork focus on harder drugs and violence. Implications for drug enforcement and criminal justice more broadly center discussion and signal future research steps.